Traditional Performing Arts and Islamization: Ricklefs' Framework Amid Historical Discontinuity in Sleman, Yogyakarta - Muhyidin (Journal of Contemporary Sociological Issues, 2025)
This research aims to explore the portrayal of Javanese traditional performing arts within Merle Calvin Ricklefs' work on the history of Islamization in Java, recognized as one of the most comprehensive historical accounts on this subject. Ricklefs' trilogy includes "Mystic Synthesis in Java: A History of Islamization from the Fourteenth to the Early Nineteenth Centuries" (2006), "Polarising Javanese Society: Islamic and Other Visions, C. 1830-1930" (2007), and "Islamisation and Its Opponents in Java: A Political, Social, Cultural, and Religious History, C. 1930 to Present" (2012). The arts are an integral part of spiritual life within Islam, flourishing among Muslim societies worldwide, including among the Javanese. One form of the arts is the performing arts, encompassing music, dance, and theater. Studies on this form of art are a crucial means of uncovering the multifaceted dynamics of Javanese society. This research employed the Foucauldian concept of historical discontinuity, utilizing content analysis as the methodological approach. This research argues that Javanese society's articulation of its arts and performances, as seen through the historical discourse of Islamization, demonstrates a dynamic evolution. Whilst continuously reinterpreting the idea of Java. To contextualize the historical account, this research examines the empirical findings among PASER (Paguyuban Seni Relijius), a performing arts group organization based in Sleman, Yogyakarta. Keywords: Arts, Discontinuity, Islam, Java, Performances